Analisis Sistem Kerja Cyber Extension Mendukung Peningkatan Keberdayaan Petani Sayuran - R. S. H. Mulyandari; Sumardjo .; D. P. Lubis; N. K. Pandjaitan (Jurnal Komunikasi Pembangunan, 2010)
Agricultural information is one of the most important factors of production and there is no doubt that this can lead todevelopment. The effective integration of Information and Communication Technologies (ICTs) in the agriculturalsector through cyber extension will lead to sustainable agriculture by providing timely and relevant agriculturalinformation, which will enable farmers make informed decisions on farming to increase productivity. The objective ofthe research is to analyze the system of cyber extension mechanism supporting the vegetable farmer empowerment.ICT application in cyber extension implementation can greatly improve farmers’ accessibility to market information,commodity inputs, and consumer trends which positively impact on the quality and the quantity of their produce.Information on marketing, new plant and animal management practice, pest and diseases, transport availability, newmarketing opportunities and market prices of farm input and output is very important to an efficient and productiveeconomy. The analysis of cyber extension mechanism was conducted based on the characteristic of system areboundary, environment, input, output, process, storage, and interface. The synergy between the subsystems to eachother is critical in the performance of the agricultural innovation process into outputs that benefit the othersubsystems. In accordance with the characteristics of the cyber extension working system in the area was influent bythe environment that produce output that is stored either permanently or temporarily. Interface is an element of thesystem to ensure the synergy among the subsystems within the system cyber extension working smoothly. Cyberextension is a communication method of agricultural innovation by using new communication media that integratesinformation technology tools to communicate information to the user faster. Therefore, analysis of the cyber extensionsystem with the black box theory illustrates the system with attention to the desired output and the output is notdesired. Mechanisms of maintenance and provision of relevant and timely input offset with socialization andassistance in the utilization of information technology for vegetable farmers in accessing information as needed is aneffort to optimize the cyber extension utilization so that it can support the empowerment process of vegetable farmers.